Decadal variability of oxygen uptake, export, and storage in the Labrador Sea from observations and CMIP6 models - Koelling, Jannes; Atamanchuk, Dariia; Wallace, Douglas W. R.; Karstensen, Johannes (Frontiers in Marine Science, 2023)
The uptake of dissolved oxygen from the atmosphere at the ocean surface and its physical transport away from the region of uptake is crucial for supplying oxygen to the deep ocean. This process, also called ventilation, takes place in a few key regions where intense oxygen uptake, deep water formation, and physical export of oxygen combine to supply oxygen to much of the global deep ocean. In this study we analyze oxygen variability in one such region, the Labrador Sea, utilizing the World Ocean Database (WOD) to construct a 65–year oxygen content time series in the Labrador Sea Water (LSW) layer (0–2200 m). The data reveal pronounced decadal variability associated with the strength of deep convection. The maximum anomaly of 30 mol m−2 in 1992 is a result of an increase in oxygen content, or ”oxygen storage”, at an average rate of 2.82mol/m2/y from 1980–1992, and is followed by a decrease of 3.05mol/m2/y from 1994–2006. We compared this time series with output from nine models of the Ocean Model Intercomparison Project phase 1 in the Climate Model Intercomparison Project phase 6, (CMIP6-OMIP1), and constructed a ”model score” to evaluate how well they reproduce the observed variability. While all models show an increase in the 1980s–1990s similar to observations, the amplitude is generally too small. Possible explanations include too little oxygen uptake, unrealistically deep convection, and biased mean oxygen profiles. Most CMIP6-OMIP1 models score around 50/100 points, with the highest score being 57/100, suggesting that improvements are needed. Refining the representation of ventilation in climate models could be vital for enhanced predictions of deoxygenation, and may also improve our understanding of deep ocean carbon cycling. In the CMIP6-OMIP1 multi-model mean, both oxygen uptake and export decrease between 1980-1992 and 1994–2006. However, oxygen storage also changes between the two periods, with oxygen accumulated in the first period and drained out in the second. Consequently, the change in oxygen export (5%) is much less than that in uptake (28%), suggesting that newly ventilated LSW which remains in the formation region acts to buffer the effect that air-sea gas exchange has on oxygen export.